2003
DOI: 10.1093/aje/kwg106
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Fields and Breast Cancer on Long Island: A Case-Control Study

Abstract: The EMF and Breast Cancer on Long Island Study (EBCLIS) was a case-control study designed to evaluate the possible association between exposure to electromagnetic fields (EMFs) and breast cancer. Eligible women were participants in the population-based Long Island Breast Cancer Study Project, were under 75 years of age at enrollment, were residentially stable, and were identified between August 1, 1996, and June 20, 1997. Of those eligible, 576 cases and 585 controls participated in EBCLIS (87% and 83%, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Since then, and over the subsequent three decades, a considerable amount of epidemiological studies have analysed a potential association with breast cancer from ELF exposure in residential and occupational environments, including from electric blankets. However, most epidemiological studies have indicated little or no overall effect of ELF-MF exposure risks and similar findings are reported in the majority of studies of bed heating devices (Verkasalo et al, 1996;Li et al, 1997;Coogan & Aschengrau, 1998;Schoenfeld et al, 2003;Elliott et al, 2013).…”
Section: Breast Cancersupporting
confidence: 70%
“…Since then, and over the subsequent three decades, a considerable amount of epidemiological studies have analysed a potential association with breast cancer from ELF exposure in residential and occupational environments, including from electric blankets. However, most epidemiological studies have indicated little or no overall effect of ELF-MF exposure risks and similar findings are reported in the majority of studies of bed heating devices (Verkasalo et al, 1996;Li et al, 1997;Coogan & Aschengrau, 1998;Schoenfeld et al, 2003;Elliott et al, 2013).…”
Section: Breast Cancersupporting
confidence: 70%
“…Three recently completed large breast cancer studies found no association with exposure to electric or magnetic fields (12,53,78).…”
Section: Effects In Adultsmentioning
confidence: 99%
“…�o augmented risk was found among women with higher exposure 38,81,83 . Occupational exposure risk was also assessed.…”
Section: Breast Cancermentioning
confidence: 94%